Yiqi Yangyin Tongluo Recipe Alleviates Diabetic Kidney Disease Through AGE-RAGE Signalling Axis - Yu R; Wu R; Chen T; Zhang Y; Chen X (Diabetes, Metabolic Syndrome and Obesity)
Rucui Yu,1 Ruiying Wu,1 Tingting Chen,1 Yan Zhang,2 Xiangqing Chen3 1Department of Traditional Chinese Medicine, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People’s Republic of China; 2Department of Anorectal, 901 Hospital of Joint Service Support Force of PLA, Hefei, 230031, People’s Republic of China; 3Department of Pharmacy, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People’s Republic of ChinaCorrespondence: Rucui Yu, Department of Traditional Chinese Medicine, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, No. 17 Lujiang Road, Luyang District, Hefei, Anhui Province, 230001, People’s Republic of China, Email yurucui_169@163.com Xiangqing Chen, Department of Pharmacy, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, No. 17 Lujiang Road, Luyang District, Hefei, Anhui Province, 230001, People’s Republic of China, Email cxqah@163.comPurpose: This study used network pharmacology to explore how Yiqi Yangyin Tongluo Formula (YQYTLF) alleviates diabetic nephropathy (DN), focusing on the AGE-RAGE signaling pathway.Methods: Active compounds and targets of YQYTLF were identified via TCMSP, and a herb-compound-target network was constructed using Cytoscape. Differentially expressed genes from DN kidney tissues (GEO dataset GSE104948) were intersected with drug targets for KEGG and GO enrichment analysis. Protein-protein interaction (PPI) networks were analyzed in STRING and visualized in Cytoscape. A DN rat model was treated with YQYTLF, with weekly monitoring of body weight, food and water intake. Fasting blood glucose (FBG), insulin (FINS), serum creatinine (Scr), blood urea nitrogen (BUN), and urinary albumin excretion rate (UAER) were measured. HOMA-β and HOMA-IR assessed beta cell function and insulin resistance. Kidney pathology was evaluated by HE and Sirius Red staining. Kidney tissue levels of AGEs, oxidative stress markers (ROS, MDA, GSH, SOD), and RAGE expression (by WB) were analyzed. Molecular docking assessed binding between active compounds and core targets.Results: Network pharmacology identified 13 core targets, 8 enriched in the AGE-RAGE pathway. YQYTLF significantly reduced FBG, FINS, Scr, BUN, UAER, HOMA-IR, renal index, and pruritus while improving HOMA-β in DN rats. Renal pathological changes including Bowman’s capsule dilation, mesangial proliferation, and fibrosis were alleviated. YQYTLF inhibited kidney AGEs, oxidative stress, and RAGE expression. Molecular docking confirmed strong binding between active ingredients and core targets.Conclusion: YQYTLF alleviates DN in rats by inhibiting AGE-RAGE pathway activation and reducing oxidative stress, providing a theoretical basis for DN therapy.Keywords: diabetes nephropathy, Yiqi Yangyin Tongluo formula, AGE-RAGE, inflammation, network pharmacology